Li-Al-CO3 LDHs type adsorption material and preparation method thereof

By using the LI-Al-Co3 LDHS adsorption material in the extraction method of carbonated salt lake lithium extraction, the use of electrolytic pure aluminum plates and lithium ion insertion reactions is used to solve the large chemical reagent consumption in the existing technology, slow synthesis rate, energy consumption, energy consumption High problems have achieved efficient and low -cost lithium extraction effects.

CN119346062APending Publication Date: 2025-01-24DONGHUA UNIV
View PDF 10 Cites 0 Cited by

Patent Information

Application Number
CN202411484270.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-23
Publication Date
2025-01-24

Smart Images

  • Figure CN119346062A_ABST
    Figure CN119346062A_ABST
Patent Text Reader

Abstract

The invention provides a Li-Al-CO3LDHs type adsorption material and a preparation method thereof, and the preparation method comprises the following steps: introducing a constant current into an aluminum electrode, and electrolyzing in an electrolyte solution to generate Al (OH) 3; the preparation method comprises the following steps: preparing a Li2CO3 solution according to a certain amount of substance ratio of Li / Al, putting Al (OH) 3 into the Li2CO3 solution for lithium ion intercalation adsorption, standing for a period of time, carrying out suction filtration, and drying a filter cake to obtain the Li-Al-CO3LDHs type adsorption material. Compared with a traditional method, the synthesis method provided by the invention has the advantages of time saving, rapidness, energy saving, environmental protection and low cost, is more suitable for extracting lithium from salt lake brine with more impurities and less lithium content, and can be put into use in industrial production.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a Li-Al-CO3 LDHs type adsorption material and a preparation method thereof, belonging to the technical field of lithium extraction from carbonate salt lakes. Background Art

[0002] Lithium metal is widely used in batteries, ceramics, glass, lubricants, refrigerants, nuclear industry, optoelectronics and other industries. With the continuous development of products such as mobile phones, digital cameras, computers, and mobile batteries, the battery industry has become the largest consumer of lithium, with its share rising from 35% in 2016 to 80% in 2023. At the same time, under the global trend of energy conservation and emission reduction, in order to reduce the adverse effects of climate change, people are trying to introduce new energy electric vehicles to minimize the exhaust emissions of fossil fuel vehicles. In addition, new energy electric vehicles will become the main development direction in the future due to their advantages of green environmental protection, energy saving and low carbon, and one of its core is new energy batteries and power battery materials, and its key raw materials are battery-grade lithium carbonate (Li2CO3).

[0003] It is reported that 70% of the raw materials for the global production of Li2CO3 come from salt lake brine and 30% from hard rock lithium ore. my country is a country with abundant salt lake brine lithium resources, and salt lake lithium resources account for more than 80% of the country's lithium resources and about 1 / 3 of the world's salt lake lithium resources. However, the calcium and magnesium ion content in my country's salt lakes is relatively high, making it difficult to extract lithium efficiently and at low cost. Therefore, the development of salt lake lithium extraction technology is imminent.

[0004] At present, the following methods are mainly used in China to extract lithium from salt lakes: such as the precipitation method provided in Publication No. CN105217665A, the extraction method provided in Publication No. CN114645144A, the electrodialysis method provided in Publication No. CN111377465A, and the calcination method provided in Publication No. CN117566804A. These methods are mature and widely used in the recovery of high-concentration lithium resources in original brine, but they are not effective for extracting lithium from brine with more impurities such as Ca, Mg, and Na and less lithium content. Therefore, the adsorption method with high enrichment ratio, high lithium extraction output, low cost and good selectivity is favored.

[0005] Common lithium adsorption materials are mainly divided into titanium-based adsorption materials (CN118497522A), manganese-based adsorption materials (CN118543334A) and aluminum-based adsorption materials (CN118531229A, CN118304853A). Aluminum-based adsorption materials are widely used in lithium extraction from salt lakes due to their advantages such as convenient preparation, high selectivity, good stability and long service life. At present, the preparation of aluminum-based adsorption materials is mainly coprecipitation method (CN117753370A) and hydrothermal synthesis (CN114053993A). A large amount of chemical reagents are required in the preparation process, and the reaction time for synthesizing a batch of adsorption materials is long, and huge energy consumption is consumed in the synthesis process. In addition, these adsorbents are mainly used for lithium extraction from salt lakes containing high concentrations of MgCl2. There is currently less public information on lithium extraction from carbonate-type salt lakes. Literature reports that Li2CO3·4Al(OH)3·3H2O adsorbent was synthesized by hydrothermal method using LiCl, AlCl3 and urea as raw materials, and applied in actual lithium extraction from carbonate salt lakes (Journal of Colloid And Interface Science, 2019, 547217-223). However, this method has the disadvantages of large consumption of chemical reagents, slow synthesis rate and high reaction energy consumption.

[0006] Therefore, it is urgent to develop an efficient and convenient adsorbent suitable for lithium extraction from carbonate salt lakes. Summary of the invention

[0007] The purpose of the present invention is to solve the problems in the prior art.

[0008] In order to achieve the purpose of solving the above problems, the technical solution adopted by the present invention is to provide a Li-Al-CO3LDHs type adsorption material and a preparation method thereof.

[0009] In a first aspect of the present invention, a method for preparing a Li-Al-CO3 LDHs type (a layered double hydroxide having a chemical formula of Li2CO3·4Al(OH)3·3H2O) adsorption material is provided, comprising the following steps:

[0010] Step 1: Grind and acid-immerse the aluminum sheet to remove the oxide film and impurities on the surface, weigh and record the mass of the anode and cathode aluminum plates.

[0011] Step 2: Prepare the electrolyte solution.

[0012] Step 3: Insert the cathode and anode plates, apply voltage, pass current, and adjust the stirring speed.

[0013] Step 4: Adjust the pH of the electrolyte, control the power-on time and reaction temperature, and prepare Al(OH)3.

[0014] Step 5. Weigh and calculate the mass and amount of dissolved aluminum.

[0015] Step 6: Prepare Li2CO3 solution and measure the lithium ion concentration.

[0016] Step 7: Place the Al(OH)3 in a Li2CO3 solution to carry out lithium ion intercalation reaction to obtain a Li-Al-CO3LDHs type adsorption material.

[0017] Preferably, in step 1, 5% to 10% H2SO4 is used for acid leaching.

[0018] Preferably, in step 2, the electrolyte solution is a Na2SO4 solution with a concentration of 50 g / L to 250 g / L or a NaNO3 solution with a concentration of 100 g / L to 400 g / L, and 25% H2SO4 is added to adjust the solution pH to 2 to 5.

[0019] Preferably, in step 3, the current is a constant current of 1 to 3A, and the stirring speed is adjusted to 50 to 300 r / min.

[0020] Preferably, in step 4, the solution pH is measured every 5 to 10 minutes during the reaction process, and the pH is controlled to be 5 to 8.5 during the entire electrocoagulation process, the electrolysis time is 30 to 60 minutes, and the temperature is 0 to 100°C.

[0021] Preferably, in step 6, the molar ratio of Li / Al is greater than or equal to 4.5:1.

[0022] Preferably, in step 7, the lithium ion intercalation reaction time is controlled within 30 to 90 minutes.

[0023] The second aspect of the present invention provides a Li-Al-CO3 LDHs type adsorption material prepared by the above method.

[0024] Compared with the prior art, the present invention has the following beneficial effects:

[0025] Aluminum comes only from electrolytic pure aluminum plates. No chemical reagents are needed to provide an aluminum source. The raw material cost is low and the electrode aluminum plates can be reused.

[0026] The synthesis rate of Li2CO3·4Al(OH)3·3H2O adsorption material is fast, requiring only 1 / 8 of the traditional hydrothermal synthesis method; the energy consumption in the preparation process is low, far less than the energy consumption of the traditional hydrothermal synthesis method.

[0027] The synthesized Li2CO3·4Al(OH)3·3H2O adsorption material has a fast adsorption rate, good elution effect, and can be recycled many times.

[0028] The raw materials for preparing the lithium adsorption material of the present invention are cheap and readily available, the adsorption rate is fast, the synthesis energy consumption is small, the synthesis rate is fast, the material is suitable for carbonate salt lakes, and the lithium extraction effect is good. BRIEF DESCRIPTION OF THE DRAWINGS

[0029] Figure 1 It is a preparation flow chart of the present invention.

[0030] Figure 2 The mechanism diagram of the present invention is

[0031] Figure 3 SEM photos of each embodiment: (a) embodiment 1; (b) embodiment 2; (c) embodiment 3; (d) embodiment 3; (e) comparative example 1; (f) comparative example 2

[0032] Figure 4 This is the XRD diffraction peak diagram of the adsorption material of the present invention.

[0033] Figure 5 This is the TEM image of the adsorption material of the present invention.

[0034] Figure 6 This is a pore size diagram of the adsorption material of the present invention taken under TEM. DETAILED DESCRIPTION

[0035] In order to make the present invention more clearly understood, a preferred embodiment is described in detail with reference to the accompanying drawings as follows:

[0036] like Figure 1-6 As shown, the present invention provides a Li-Al-CO3 LDHs type adsorption material and a preparation method thereof.

[0037] Embodiment 1:

[0038] A method for preparing a lithium adsorption material comprises the following steps:

[0039] Step 1) Take two 1*25*100 mm pure aluminum sheets, soak them in 10% H2SO4 for 15 min, then clean the surface with deionized water and dry them.

[0040] Step 2) Prepare 40g / 200ml Na2SO4 solution as electrolyte solution, connect the aluminum sheet in step 1 to a power source and place it in the solution.

[0041] Step 3) Control the plate spacing to 1 cm, pass a constant current of 2 A, adjust the stirring speed to 150 r / min, heat the solution to 80°C, and after electrolysis for 60 minutes, a large amount of white Al(OH)3 is deposited in the solution, and the reaction endpoint pH is 10.5.

[0042] Step 4) Take out the aluminum plate after the reaction in step 3, rinse it and weigh it, calculate the mass of dissolved aluminum to be 1.11g, prepare 6.85g / 700ml Li2CO3 solution according to the Li / Al molar ratio of 4.5 / 1, and place Li2CO3 in an ice-water mixture.

[0043] Step 5) Slowly drip the icy Li2CO3 solution into the 80°C Al(OH)3 solution, and control the stirring speed to 300 r / min.

[0044] Step 6) The mixed solution was filtered and dried to obtain 3.03 g of adsorption material.

[0045] Comparative Example 1:

[0046] Step 1) Take two 1*25*100 mm pure aluminum sheets, soak them in 10% H2SO4 for 15 minutes, then clean the surface with deionized water and dry them.

[0047] Step 2) Prepare 40g / 200ml Na2SO4 solution and add 25% H2SO4 to adjust the pH to 2.94.

[0048] Step 3) Weigh and record the mass of the aluminum sheet after drying in step 1), connect them to a power source as anode and cathode plates respectively, control the plate spacing to be 1 cm, pass a constant current of 2 A, and adjust the stirring speed to 150 r / min.

[0049] Step 4) This reaction was carried out in an ice-water mixture. During the reaction, the pH of the solution was measured every 5 minutes. If the pH>8.5, 25% H2SO4 was added to reduce it. After 60 minutes of electrolysis, a large amount of white flocculent Al(OH)3 was obtained. The reaction end point pH was 6.55.

[0050] Step 5) Take out the aluminum plate after the reaction in step 4), rinse it and weigh it, calculate the mass of dissolved aluminum to be 0.63g, and prepare 3g / 450ml Li2CO3 solution according to the Li / Al molar ratio of 3.475 / 1.

[0051] Step 6) Filter out the Al(OH)3 in step 4, put it into the Li2CO3 solution prepared in step 5), adjust the stirring speed to 250r / min, stir for 60min and then filter, and obtain 2.84g of adsorption material after drying.

[0052] Comparative Example 2

[0053] A method for preparing a lithium adsorption material comprises the following steps:

[0054] This embodiment is the same as Comparative Example 1, except that the Li / Al material ratio is controlled to be 1.5 / 1.

[0055] Comparative Example 3

[0056] A method for preparing a lithium adsorption material comprises the following steps:

[0057] Step 1) Take two 1*25*100 mm pure aluminum sheets, soak them in 10% H2SO4 for 15 min, then clean the surface with deionized water and dry them.

[0058] Step 2) Prepare 40g / 200ml NaNO3 solution as electrolyte solution, add 15g NaHCO3 and stir to mix, the pH of the mixed solution is 9.8, then connect the aluminum sheet in step 1 to a power source and place it in the solution.

[0059] Step 3) Control the plate spacing to 1 cm, adjust the stirring speed to 150 r / min at 25°C. Turn on the power supply and apply a constant current of 2A. During the reaction, measure the solution pH every 5 minutes. If the pH is > 8.5, add 10% HNO3 to reduce it. After 60 minutes of electrolysis, filter and obtain a large amount of white flocculent Al(OH)3. The reaction end point pH is 6.39.

[0060] Step 4) Take out the aluminum plate after the reaction in step 3, rinse it and weigh it, calculate the mass of dissolved aluminum to be 1g, prepare 5g / 500ml Li2CO3 solution according to the Li / Al molar ratio of 3.65 / 1, put the solid filtered in step 3 into the prepared Li2CO3 solution, and control the stirring rate to 250r / min.

[0061] Step 5) The solution after the reaction in step 4 was filtered and dried to obtain 3.67 g of adsorption material.

[0062] Comparative Example 4:

[0063] A method for preparing a lithium adsorption material comprises the following steps:

[0064] This embodiment is the same as Comparative Example 3, except that the Li / Al material ratio is controlled to be 3.0 / 1.

[0065] SEM test:

[0066] The lithium adsorption materials prepared in each embodiment were tested by scanning electron microscopy (SEM), and the test results are shown in the attached drawings of the specification.

[0067] Through observation, it can be seen that after the improved scheme is magnified by 50k times, the structure of each layer of the adsorption material is clearer and the ion vacancies are more obvious. Obviously, the adsorption material prepared by the improved scheme is purer.

[0068] Therefore, the following analysis and testing mainly revolves around the improved solution.

[0069] By observing and analyzing the SEM photos of Example 3, Comparative Example 1 and Comparative Example 2, it can be seen that when the amount ratio of Li / Al substances is larger, the structure displayed in the SEM photos is more obvious, and the petal-like structure of the adsorption material can appear at a smaller magnification.

[0070] XRD test:

[0071] The lithium adsorption materials obtained in the improved Example 1 and Comparative Examples 2 and 4 were tested by X-ray powder polycrystalline diffractometer (XRD).

[0072] After comparing the materials through Jade, it was found that only the diffraction peak of Example 1 showed the absorption peak of Li2CO3·4Al(OH)3·3H2O. However, only the absorption peaks of AlO(OH) and LiAl2(OH)7·2H2O appeared in Comparative Examples 2 and 4. 2- Intercalation was not successfully achieved.

[0073] By comparing and analyzing the above results, it can be obtained that during the preparation process, the product adsorption material can be obtained by ensuring that the Li / Al substance ratio is above 4.5. When the Li / Al substance ratio is less than 3.0, the intercalation is incomplete and the crystal structure is not fully grown.

[0074] The following table shows the absorption peak data of Li2CO3·4Al(OH)3·3H2O prepared in Example 1:

[0075]

[0076] A comprehensive comparison of the XRD diffraction peak diagram and the data in the table above shows that there are two obvious characteristic peaks at 11.7° and 23.5°, corresponding to the (003) and (006) crystal planes, respectively. In addition, the arrangement of the (003) and (006) crystal planes, as shown by d(003)=2d(006), confirms the layered structure of the material.

[0077] The above is only a preferred embodiment of the present invention, and is not any formal or substantial limitation of the present invention. It should be pointed out that ordinary technicians in this technical field can make several improvements and supplements without departing from the present invention, and these improvements and supplements should also be regarded as the protection scope of the present invention. Any technician familiar with this profession, without departing from the spirit and scope of the present invention, can make some changes, modifications and equivalent changes made by using the technical content disclosed above, which are equivalent embodiments of the present invention; at the same time, any changes, modifications and evolutions of any equivalent changes made to the above embodiments based on the essential technology of the present invention are still within the scope of the technical solution of the present invention.

Claims

1. A method for preparing a Li-Al-CO3 LDHs type adsorption material, characterized in that: The following steps are involved: Step 1: Grind and acid-immerse the aluminum sheet to remove the oxide film and impurities on the surface, and weigh and record the mass of the cathode and anode aluminum plates; Step 2, preparing an electrolyte solution; Step 3, insert the cathode and anode plates, apply voltage, pass current, and adjust the stirring speed; Step 4: adjust the pH of the electrolyte, control the power-on time and the reaction temperature, prepare Al(OH)3, and filter; Step 5, weigh and calculate the mass and amount of dissolved aluminum; Step 6: Prepare Li2CO3 solution and measure the lithium ion concentration; Step 7: placing the Al(OH)3 in a Li2CO3 solution to carry out lithium ion intercalation reaction to obtain a Li-Al-CO3 LDHs type adsorption material.

2. The method for preparing the Li-Al-CO3 LDHs type adsorbent material according to claim 1, characterized in that: In the step 1, 5% to 10% H2SO4 is used for acid leaching.

3. The method for preparing the Li-Al-CO3 LDHs type adsorbent material according to claim 1, characterized in that: In the step 2, the electrolyte solution is a Na2SO4 solution with a concentration of 50g / L to 250g / L or a NaNO3 solution with a concentration of 100g / L to 400g / L, and 25% H2SO4 is added to adjust the solution pH to 2 to 5.

4. The method for preparing the Li-Al-CO3 LDHs type adsorbent material according to claim 1, characterized in that: In the step 3, the current is a constant current of 1 to 3A, the stirring speed is adjusted to 50 to 300 r / min, and the applied voltage is 20 to 40V.

5. The method for preparing the Li-Al-CO3 LDHs type adsorbent material according to claim 1, characterized in that: In the step 4, the solution pH is measured every 5 to 10 minutes during the reaction process, and the pH is controlled at 3 to 7 during the entire electrocoagulation process, the electrolysis time is 30 to 60 minutes, and the temperature is 80 to 100°C.

6. The method for preparing the Li-Al-CO3 LDHs type adsorbent material according to claim 1, characterized in that: In step 6, the molar ratio of Li / Al is greater than or equal to 4.5:

1.

7. The method for preparing the Li-Al-CO3 LDHs type adsorbent material according to claim 1, characterized in that: In step 7, the lithium ion intercalation reaction time is controlled within 30 to 90 minutes.

8. A Li-Al-CO3LDHs type adsorbent material obtained by the preparation method according to any one of claims 1 to 7.

Citation Information

Patent Citations

  • Method for reducing magnesium-to-lithium ratio of salt lake brine with high magnesium-lithium ratio

    CN105217665A

  • Method for preparing battery-grade lithium carbonate from lepidolite

    CN111377465A

  • Preparation method of aluminum-based layered lithium adsorbent

    CN114053993A

  • Method for extracting lithium by using deep eutectic solvent

    CN114645144A

  • Preparation method of porous spherical manganese lithium ion sieve adsorbent

    CN117566804A